Studies on atmospheric particulate matter at Delhi (MAUSAM, 1965)
Making use of a simple technique, a study has been made on a number of days spread over a period of 20 months during 1960-62, of the concentration of nitrate, chloride and sulphate particles in the atmosphere in ground air layers at Delhi. In general, nitrates or nitrate containing other salts (mixed nuclei) are found to predominate over both chlorides and sulphates. All the three components appear to have a common origin which is, perhaps, the sea. The concentrations are seen to decrease by about two orders of magnitude during winter and summer as compared to the monsoon season.